Efektifitas Pembiayaan Modal Usaha Oleh Baitul Mal Aceh Terhadap Usaha Agribisnis - Hendra Kusumah; Mustafa Usman; Fajri Fajri (Jurnal Bisnis Tani, 2018)
One of the main problems in the development of the agricultural sector is the lack of capital.Baitul Mal Aceh as one of the Zakat Management Board has issued productive zakat used for business activities.The results showed that the implementation of agribusiness-based business financing program by Baitul Mal Aceh has been effective with the form of qardul hasan or without interest and profit sharing,business capital is revolving,the amount of business capital financing varies from Rp 2.000.000, - - Rp 10.000.000, -, this has an impact on the increase of income mustahik from Rp 2.300.000 - Rp 10.000.000, -From the time side of the mustahik return the current collectability is 91.04%,less current 5.67%,Doubtful 3.28% and no business returns are stalled.The average income of the mustahik after receiving agribusiness-based business financing of Rp 4.310.000 has fulfilled the Decent Living Needs. Revenue mustahik be better since the existence of such financing activities and give multiplier effect to the previous income with an average amount of Rp 2,261,429. The increase of income of the mustahik in the research is 100.75%.